A Comparative Study of Food Source Selection in Stingless Bees and Honeybees: Scent Marks, Location, or Color - Koethe, Sebastian; Fischbach, Vivian; Banysch, Sarah; Reinartz, Lara; Hrncir, Michael; Lunau, Klaus (Frontiers in Plant Science, 2020)
In social bees, the choice of food sources is based on several factors, including scent marks, color, and location of flowers. Here, we used similar setups, in which two stingless bee species, Melipona subnitida and Plebeia flavocincta, and the Western honeybee, Apis mellifera, were tested regarding the importance of chemical cues, color cues, and location-dependent cues for foraging behavior. It was determined whether workers chose food sources according to (1) scent marks deposited by conspecifics, (2) the color hue of a food source, (3) the trained location or the proximity of a food source to the hive. All three species preferred the scent-marked over an unmarked feeder that was presented simultaneously, but M. subnitida showed a weaker preference compared to the other species. When trained to blue feeders all three bee species preferred blue, but A. mellifera showed the strongest fidelity. The training to yellow feeders led to less distinct color choices. Only workers of M. subnitida mostly orientated at the training position and the close proximity to the nest. Whether the distance of a feeding site influenced the choice was dependent on the tested parameter (color or scent marks) and the species. Workers of M. subnitida preferably visited the feeder closer to the nest during the scent mark trials, but choose randomly when tested for color learning. Worker honeybees preferred the closer feeding site if trained to yellow, but not if trained to blue, and preferred the more distant feeder during the scent mark trials. Workers of P. flavocincta preferred the closer feeder if trained to blue or yellow, and preferred the more distant feeder during the scent mark trials. The disparity among the species corresponds to differences in body size. Smaller bees are known for reduced visual capabilities and might rely less on visual parameters of the target such as color hue, saturation, or brightness but use scent cues instead. Moreover, the dim-light conditions in forest habitats might reduce the reliability of visual orientation as compared to olfactory orientation. Honeybees showed the most pronounced orientation at floral color cues.